Effect of Parameter Modification on Torque Ripple in Interior Permanent Magnet Synchronous Motor - Achmad Zuchriadi; Muhamad Alif Razi; Farha, Auditya; Ferdyanto (Emitor: Jurnal Teknik Elektro, 2024)
Electric motors are electromechanical machines commonly used in industry and automotive products. Interior Permanent Magnet Synchronous Motor (IPMSM) is a synchronous electric motor with a permanent magnet that is often used on electric vehicle engines. However, one of the characteristics of an electric motor with permanent magnet is the existence of torque ripples. The presence of torque ripples in electric motors can cause vibrations in the machine which affect efficiency, structural durability and operating speed. Therefore, it is necessary to make improvements or changes to the motor design to overcome this problem. This study was conducted to analyze the effect of a modification of the electric motor parameter on the torque value in the existing design. Modifications are applied to the existing design with an initial condition of torque ripples of 42.58%. This study modified the air gap, magnet angles, magnet thickness, and opening slot width. Modifications are carried out through a finite element method-based software simulation with the Taguchi method to reduce experimental configurations of design factors from 625 to 25 experiments. Through this research on parameter modification, the results of the analysis show that each modification of the design factor has an influence on the value of torque ripples. From the process of Analysis of Mean (ANOM), it can be seen that wider air gap and slot opening, the smaller torque ripples. Then, the greater magnet rib and thicker magnet cause the greater torque ripples.